Penerapan Teori Pembelajaran Kognitif dalam Meningkatkan Semangat Belajar IPA Siswa Kelas VI Sekolah Dasar - Yasrini, Dewa Ayu; Suarni, Ni Ketut; Margunayasa, I Gede (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of the study was to measure the impact of the application of cognitive learning theory on the spirit of learning, as well as integrate qualitative and quantitative approaches to gain a holistic understanding. This study used a quasi-experimental design with two groups of students as research subjects, where the experimental group received an intervention with a cognitive learning model, while the control group followed conventional learning. Data was collected through pre-test, post-test, and spirit of learning questionnaires. Data analysis involves T test for quantitative data and thematic analysis for qualitative data. The results showed a significant increase in the enthusiasm of students who followed the cognitive learning model, along with positive changes in students' perceptions and experiences of science learning.